Fenomena Kekuatan Laba di Masa Covid-19: Suatu Pengujian Keputusan Pembiayaan Utang dan Tindakan Penghindaran Pajak - Elia Rossa (Studi Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This study aims to determine the effect of debt financing decisions and tax avoidance actions on earnings power during the COVID-19 period. Method: The sample of this study uses the property and real estate sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2020. The sample determination uses the purposive sampling method, so that this study obtains a final sample of 33 issuers. The analytical tool used to test the hypothesis is eviews version 11. Results: This study finds that debt financing decisions and tax avoidance have a negative and significant effect on earnings power during the COVID-19 period. Limitations: This study found that debt financing decisions and tax avoidance measures can only affect profit strength during the Covid-19 period by 14,07%. This condition shows that there are other variables that can affect the phenomenon of earnings power during the Covid-19 period, but are not included in this study. In addition, this study is limited to using a final sample of 33 companies out of a total of 77 companies in the property and real estate sub-sector due to the large number of issuers who suffered losses during the COVID-19 period. Contribution: to companies belonging to the property and real estate sub-sector as a form of evaluation of low earning power that can be influenced by debt financing decisions and tax avoidance actions. In addition, this study can also be used as a reference for companies that have the potential to experience a crisis in deciding whether or not to take action to finance debt and even avoid tax. This study also seeks to fill the void of previous studies which were still limited to examining the effect of debt financing decisions and tax avoidance measures on profit strength during the Covid-19 period by involving the property and real estate sub-sectors that had the most impact on the Covid-19 condition.